Diagnostic Yield of Bronchoalveolar lavage Xpert MTB/RIF Assay (Gene Xpert ® in Sputum Smear Negative Pulmonary Tuberculosis Patients – A One Year Cross Sectional Study (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: Tuberculosis remains a major public health issue and is one of the top ten causes of death worldwide. Seven countries worldwide account for 64% of the total incidence and India leading the count. Only about 50-60% of the cases are sputum smear positive, while rest are sputum scare or smear negative cases. Since December 2010, WHO has recommended the use of Xpert MTB/RIF assay due to its high-quality performance, as compared to microscopy in the diagnosis of tuberculosis. The present study was done to evaluate the early diagnosis of sputum smear negative pulmonary tuberculosis patients using Xpert MTB/RIF assay test in broncho-alveolar fluid and to evaluate prevalence of rifampicin resistance in these patients.Methods: This was a one year cross section study conducted in a tertiary care hospital. A total of 143 suspected cases of pulmonary tuberculosis patients who were sputum smear negative were included in the study. All patients underwent bronchoscopy and the BAL specimen was subjected for Xpert MTB/RIF assay, smear by ZN staining and AFB Culture using MGIT 960 medium. The sensitivity and specificity of the Xpert MTB/RIF assay was compared to AFB culture which is considered as the gold standard method for diagnosing TB was calculated.Results: Majority of the patients were males (74.83%) and under the age group of 30 years (26.57%). Out of 143 suspected, the final diagnosis of PTB was done in 93 patients. Out of 93 cases of PTB, 87(93.5%) patients were Xpert MTB/RIF assay positive, 80(86.0%) were AFB culture positive and 39(41.9%) patients were AFB smear positive. The sensitivity and specificity of BAL Xpert MTB/RIF assay was 92.5% and 79.37% respectively (p